Effect of pipeline surface roughness on peak impact forces caused by hydrodynamic submarine mudflow. (1st January 2022) - Guo, Xingsen; Stoesser, Thorsten; Nian, Tingkai; Jia, Yonggang; Liu, Xiaolei
Abstract: The effect of pipeline surface roughness on the interaction between submarine landslides and pipelines may not be insignificant and has rarely been quantified. In this paper, a previously validated computational fluid dynamics model is employed to study the interaction of submarine landslides and suspended or laid-on-seabed pipelines, respectively, which are roughened in order to quantify the effect of pipeline surface roughness. Here, four orders of magnitude surface roughnesses are chosen whereas the mudflows (submarine landslides) occur at typical Reynolds numbers. The effect of surface roughness is primarily reflected in the peak load of the impact forces on the pipelines, which are more sensitive to high Reynolds numbers and suspension conditions. For suspended pipelines, with the increase of roughness, (i) the peak lift force increases, (ii) the peak drag force decreases, and (iii) Strouhal number slightly increases. Compared with nearly smooth pipelines, the relative increase of the peak lift force and the relative reduction of the peak drag force on suspended pipelines with a surface roughness of 0.15 mm attain 62% or 17%, respectively. Additionally, relevant mechanisms are highlighted via contours of the pressure around the pipeline, the interfacial shear rate, as well as the squeeze and hindrance effect of the seabed. Further, a standard chart methodology considering pipeline roughness to estimate peak impact forces is established, which provides a basis for the risk assessment of the whole life cycle of submarine pipelines. Highlights: The effect of pipeline surface roughness on impact forces on suspended and laid-on-seabed pipelines caused by mudflows are quantified. The mechanisms of surface roughness on the interface contact of submarine mudflows impact on pipelines are explained. The variation of Strouhal number for assessing flow-induced vibrations on the suspended pipeline is given. A methodology to estimate the peak drag and lift forces considering the pipeline surface roughness is established.